Effects of two-stage preterm formulas on growth, nutritional biomarkers, and neurodevelopment in preterm infants - Przemko Kwinta; Svilena Lazarova; Klaudia Demová; Yipu Chen; Mickaël Hartweg; Laura-Florina Krattinger; Cecilia Fumero; Aleksandra Buczyńska; Wojciech Durlak; Zuzana Uhrikova; Marek Kozar; Tinu Mary Samuel; et al. (Frontiers in Pediatrics)
BackgroundFormula-fed preterm infants require nutrient-enriched formulas with optimized protein levels to support growth and neurodevelopment. The purpose of this study was to evaluate the safety, tolerability, and effectiveness of a new liquid two-staged formula system designed to provide tailored nutrition during hospital stay and after discharge.MethodsMale and female very-low-birth-weight preterm infants (birth weight ≤1,500 g; gestational age ≤32 weeks) were recruited from three neonatal units in Poland and Slovakia in a prospective, open-label, interventional study. Stage 1 formula providing 3.6 g intact protein/100 kcal was consumed from enrollment until reaching 1,800 g, followed by a post-discharge (PD) Stage 2 formula with 2.8 g/100 kcal protein, which was consumed for 30 days. Weight gain velocity (WGV in g/kg/day) between the first day of achieving full enteral feeding (FEF D1 rate of 150 ml/kg/day and cessation of parenteral feeding) and day reaching 1,800 g was compared to the minimally required WGV (15 g/kg/day) for non-inferiority (primary endpoint), and to the Fenton median growth rate for superiority (17.3 g/kg/day), adjusting for sex, gestational age, site, visit, and WGV. Changes in z-scores, feeding tolerance, nutritional biomarker status, and safety were also assessed from FEF D1 to 30 days PD. In an observational follow-up at 2 years of age, neurodevelopment was evaluated using the Bayley Scales of Infant and Toddler Development (BSID-III).ResultsAdjusted weight gain velocity (95% CI) between the first day of full enteral feeding and day reaching 1,800 g in per protocol (PP, N = 18) was 23.0 (20.1–25.9) g/kg/day; lower limit of the 95% CIs exceeded the non-inferiority margin (15 g/kg/day, p < 0.001) and the superiority margin (17.3 g/kg/day, p < 0.001). Mean stool frequency ranged from 2.5 to 3.3 stools per day. The two-stage formula supported adequate growth patterns throughout the study and nutritional biomarkers of protein and mineral status were within normal ranges. At 24 months corrected age, the mean ± SD of the BSID cognitive scale was 97.3 ± 13.9 in PP, with all infants achieving a score >70. None of the adverse events reported were related to the study formulas.ConclusionThe two-stage preterm formulas supported postnatal weight gain, adequate growth, cognitive development within normal ranges, and a safe profile of protein and bone biomarkers. Clinical Trial RegistrationClinicaltrials.gov registration, NCT03728764, NCT04962035.